Death of a unicorn [videorecording (Blu-Ray)] - Scharfman, Alex; Rudd, Paul; Ortega, Jenna; Poulter, Will; Carrigan, Anthony, 1983-; Mani, Sunita; Park, Stephen, 1951-; Hynes, Jessica, 1972-; Leoni, Téa, 1966-; Grant, Richard E., 1957-; Fong, Larry; Romer, Dan; et al. (A24, 2025)
A father and daughter accidentally hit and kill a unicorn while on a weekend retreat, where his billionaire boss seeks to exploit the creature's miraculous curative properties. While the family plans a prosperous future, the baby unicorn's family seeks deadly revenge.